Safety investment optimization in process industry: A risk-based approach. (January 2020) - Roy, Sandip; Gupta, Ankit
Abstract: Process plant safety is a critical indicator of organizational performance. Adequate investment into safety practices to avoid future accident cost is therefore a beneficial strategy. The current approach to such investments in the process industry is driven largely by simple risk-based heuristics, insurance market premiums, organizational culture and management judgment. There is, however, an absence of an overarching methodology to assist such an effort. Therefore, there is a need for developing a robust decision-making framework for enabling systematic and optimal allocation of financial resources across all significant risk elements within a process plant. The present work proposes a safety investment optimization (SIO) framework for a typical process plant. Such an optimization approach targets maximal reduction of risk values across all potential hazards within the constraint of a given safety investment budget at the incipient stage of establishing a plant such that it saves future cost to company by reducing the risk from accidents. At the same time the framework takes into account the need to comply with the regulatory requirements imposed by the government. Additionally, access to insurance market as a strategy to transfer risk is also integrated. Finally, the residual risks are managed through investments in selective safeguards while ensuring that the benefits over-weigh the cost of such an exercise. For illustrating the application of the framework, a representative process plant with a select number of risk scenarios is chosen and all steps suggested by the framework are demonstrated quantitatively. It is anticipated that the proposed SIO framework will help optimal resource allocation for managing the risks implicit in a typical process plant. Highlights: It is necessary to allocate monetary resources across all risk sources such that future costs of accidents are avoided. The proposed safety investment optimization (SIO) method first reduces the public individual risk to an acceptable value. Secondly, selection of appropriate insurance policy is undertaken for select residual risks. Lastly, for the remaining risk sources the most cost-effective combination of safeguards are chosen. A simplified case study is used to illustrate the overall SIO approach.